Fluoride Release, Radiopacity and Rugosity in Glass Ionomer Surfaces Subjected to pH Cycling - Guisso, Luigi Pedrini; Santod, Paulo Henrique dos; Salzedas, Leda Maria Pescinini; Ostini, Denise Pedrini; Guedes, Ana Paula Albuquerque; Suzuki, Thaís Yumi Umeda; Hosida, Thayse Yumi; Delbem, Alberto Carlos Botazzo (ARCHIVES OF HEALTH INVESTIGATION, 2025)
The aim of this study was to evaluate fluoride release, radiopacity and rugosity in glass ionomer surface of four restorative glass ionomer cements subjected to pH cycling. Six specimens from each experimental group (Ketac N100, Vitremer, Riva Light Cure, Fuji IX, Riva Self Cure) were first immersed in 2mL of demineralizing solutions (De) for six hours and then placed in the remineralizing solution (Re) for eighteen hours, this cycle repeated for 7 days. Radiopacity and roughness were measured at the beginning and end of cycling. The fluoride released in the Des- and Re- solutions was analyzed at 24-hour intervals over the 7 days. The data were submitted to two-way ANOVA and Fisher's PLSD test (p<0.05). The Ketac N100 group showed lower roughness and greater radiopacity before and after pH cycling, when compared to the other groups (p<0.05). All glass ionomer cements evaluated showed greater fluoride release on the first day of cycling. The Riva Light Cure, Vitremer and Fuji IX groups had a higher mean fluoride release during the 7 days of cycling when compared to Ketac N100. It was concluded that Ketac N100 presented, before and after cycling, lower roughness and greater radiopacity when compared to the other groups. In addition, it presented fluoride released higher than Riva Light Cure (SDI-L) and Riva Self Cure (SDI-S), but similar to Vitremer (VIT) and Fuji IX (F9).